One to one maths interventions built for KS4 success

Weekly online one to one GCSE maths revision lessons now available

In order to access this I need to be confident with:

Rearranging equations Expanding brackets Simultaneous equations Quadratic equations (factorising) Quadratic formulaThis topic is relevant for:

Here is everything you need to know about quadratic simultaneous equations for GCSE maths (Edexcel, AQA and OCR).

You’ll learn what quadratic simultaneous equations are and how to solve them algebraically. We will also discuss their relationship to graphs and how they can be solved graphically.

Look out for the quadratic simultaneous equations worksheets and exam questions at the end.

Quadratic simultaneous equations are two or more equations that share variables that are raised to powers up to ^{2}^{2}

Below are examples of quadratic simultaneous equations that are made up of a pair of equations; one linear equation and one quadratic equation.

\[\begin{aligned}
y&=x+3 \\
y&=x^{2}+5 x-2
\end{aligned}\]

\[\begin{aligned}
y^{2}+x^{2}&=29 \\
x+7 \quad&=y
\end{aligned}\]

\[\begin{aligned}
2 x^{2}-8 y^{2}&=18 \\
3 x+4 y&=7
\end{aligned}\]

One key difference of quadratic simultaneous equations is that we can expect multiple answers. This is because of the way the graphs of linear and quadratic functions can intersect.

On the graph below we can see the straight line of the linear equation has crossed the curved parabola of the quadratic equation at two points of intersection.

This means the simultaneous equations have two valid answers.

These points of intersection are the solutions to the simultaneous equations.

E.g. Solve

\[\begin{aligned}
x+y &=6 \\
y &=x^{2}-4 x-2
\end{aligned}\]

When graphed these two equations intersect at two points **(− 6, 10)****(1, 3)**

So the solutions to the simultaneous equations are:

\[x = -6, y = 10\]

and

\[x = 1, y = 3\]

Get your free quadratic simultaneous equations worksheet of 20+ questions and answers. Includes reasoning and applied questions.

DOWNLOAD FREEGet your free quadratic simultaneous equations worksheet of 20+ questions and answers. Includes reasoning and applied questions.

DOWNLOAD FREEIf you’re looking for an introduction to solving simultaneous equations and a step by step guide to solving simultaneous equations graphically then you may find it helpful to start with our other lessons in this section.

To solve a set of simultaneous equations you need to:

- Eliminate one of the variables.
- Find the value of one variable.
- Find the value of the remaining variables via substitution.
- Clearly state the final answer/s.
- Check your answer by substituting both values into either of the original equations.

See below for example solutions to three common forms of simultaneous equations involving quadratics.

**Step by step guide:**Substitution

Solve:

\[\begin{array}{l}
y=x+3 \\
y=x^{2}+5 x-2
\end{array}\]

- Eliminate one of the variables.

We can use the fact that

\[\begin{array}{l}
y=x+3 \\
y=x^{2}+5 x-2
\end{array}\]

Therefore

\[x+3=x^{2}+5 x-2\]

Another way to think about this is that as both equations are equal to

2Find the value of one variable.

As the equation is now quadratic we should make the equation

\[\begin{aligned}
x+3 &=x^{2}+5 x-2 \\
0 &=x^{2}+4 x-5 \\
0 &=(x+5)(x-1)\\
x&=-5\quad or \quad x=1
\end{aligned}\]

*NOTE: remember we are subtracting the whole of − (x + 3).*

*NOTE: here we have solved by factorising but you could also solve by using the quadratic equation or by completing the square.*

*NOTE: we have found two possible values of x by using the quadratic equation.*

3Find the value of the remaining variables via substitution.

As we have two values of

Remember you can use either equation, so why not pick the easiest!

\[y=x+3\]

\[\begin{aligned}
x&=-5 \\
y&=x+3 \\
y&=-5+3 \\
y&=-2
\end{aligned}\]

\[\begin{aligned}
x&=1 \\
y&=x+3 \\
y&=1+3 \\
y&=4
\end{aligned}\]

4Clearly state the final answer/s.

\[x=-5,y=-2\]

or

\[x=1,y=4\]

5Check your answer by substituting both values into either of the original equations.

\[y=x^{2}+5 x-2\\
x=-5, \quad y=-2\]

\[\begin{array}{l}
-2=(-5)^{2}+5(-5)-2 \\
-2=25-25-2
\end{array}\]

\[y=x^{2}+5 x-2\\
x=1, \quad y=4\]

\[\begin{array}{l}
4=(1)^{2}+5(1)-2 \\
4=1+5-2
\end{array}\]

Both are valid so we can be confident our answer is correct.

When graphed these two equations intersect at

\[x=-5,y=-2\]

or

\[x=1,y=4\]

Solve:

\[\begin{aligned}
y^{2}+x^{2}&=29 \\
x+7&=y
\end{aligned}\]

Eliminate one of the variables.

We can use the fact that

\[\begin{aligned}
y^{2}+x^{2}&=29 \\
x+7&=y
\end{aligned}\]

Therefore

\[(x+7)^{2}+x^{2}=29\]

Find the value of one variable.

As the equation is now quadratic we should make the equation

\[\begin{aligned}
(x+7)^{2}+x^{2}&=29 \\
x^{2}+7 x+7 x+49+x^{2}&=29 \\
2 x^{2}+14 x+49&=29 \\
2 x^{2}+14 x+20&=0 \\
x^{2}+7 x+10&=0 \\
(x+5)(x+2)&=0 \\
x&=-5\quad or \quad x=-2
\end{aligned}\]

*NOTE: remember (x + 7)*

*NOTE: we can simplify by ÷ 2.*

*NOTE: we have found two possible values of x by using the quadratic equation.*

Find the value of the remaining variables via substitution.

As we have two values of

Remember you can use either equation, so why not pick the easiest!

\[x+7=y\]

\[\begin{aligned}
x&=-5\\
x+7&=y\\
-5+7&=y\\
2&=y
\end{aligned}\]

\[\begin{aligned}
x&=-2\\
x+7&=y\\
-2+7&=y\\
5&=y
\end{aligned}\]

Clearly state the final answer.

\[x=-5,y= 2\]

or

\[x=-2,y=5\]

Check your answer by substituting both values into either of the original equation.

\[y^{2}+x^{2}=29\\
x=-5, \quad y=-2\]

\[\begin{aligned}
2^{2}+(-5)^{2}&=29 \\
4+29&=29
\end{aligned}\]

\[y^{2}+x^{2}=29\\
x=-5, \quad y=-2\]

\[\begin{aligned}
5^{2}+(-2)^{2}&=29 \\
25+4&=29
\end{aligned}\]

Both are valid so we can be confident our answer is correct.

Graphical representation

When graphed these two equations intersect at

\[x=-5,y= 2\]

or

\[x=-2,y=5\]

Notice that the graph of ^{2} + x^{2} = 29

Solve:

\[\begin{aligned}
2 x^{2}-8 y^{2} &=18 \\
3x+4y &=7
\end{aligned}\]

Eliminate one of the variables.

Firstly we need to make

\[\begin{aligned}
3 x+4 y &=7 \\
4 y &=7-3 x \\
y &=\frac{7-3 x}{4}
\end{aligned}\]

We can use the fact that

\[y=\frac{7-3 x}{4}\]

to substitute the value of

\[y=\frac{7-3 x}{4}\\
2x^{2}-8 y^{2}=18\]

Therefore

\[2 x^{2}-8(\frac{7-3 x}{4})^{2}=18\]

Find the value of one variable.

As the equation is now quadratic we should make the equation

\[\begin{aligned}
2x^{2}-8\left(\frac{7-3 x}{4}\right)^{2} \quad&=18 \\
2x^{2}-8\left(\frac{7-3 x}{4}\right)\left(\frac{7-3 x}{4}\right)&=18 \\
x^{2}-8\left(\frac{49-21 x-21 x+9 x^{2}}{16}\right)&=18\\
2x^{2}-8\left(\frac{49-42 x+9 x^{2}}{16}\right)&=18 \\
4x^{2}-\left(49-42 x+9 x^{2}\right)&=36 \\
4x^{2}-49+42 x-9 x^{2}&=36 \\
-49+42 x-5 x^{2}&=36 \\
42x-5x^{2} &=85\\
-5x^{2} &=85-42x\\
0 &=5 x^{2}-42 x+85
\end{aligned}\]

NOTE: multiply each term by

NOTE: be careful of the negatives.

NOTE: equate to

This equations appears harder to factorise so we can also use the quadratic formula.

\[\begin{aligned}
0&=5 x^{2}-42x+85 \\
a&=5, b=-42, c=85 \\
x&=-b \pm \frac{\sqrt{b^{2}-4 a c}}{2 a} \\
x&=-(-42) \pm \frac{\sqrt{(-42)^{2}-4(5)(85)}}{2(5)} \\
x&=3.4, \qquad x=5
\end{aligned}\]

Notice that the solutions can be decimals as well as integers.

Find the value of the remaining variables via substitution.

As we have two values of

Remember you can use either equation, so why not pick the easiest!

\[\begin{aligned}
x&=3.4\\
3x+4y&=7\\
3(3.4)+4y&=7\\
10.2+4y&=7\\
4y&=-3.2\\
y&=-0.8
\end{aligned}\]

\[\begin{aligned}
x&=5\\
3x+4y&=7\\
3(5)+4y&=7\\
15+4y&=7\\
4y&=-8\\
y&=-2
\end{aligned}\]

Clearly state the final answer/s.

\[x= 3.4,y=-0.8\]

or

\[x=5,y=-2\]

Check your answer by substituting both values into either of the original equation.

\[2x^{2}-8y^{2}=18\\
x=3.4, \quad y=-0.8\]

\[\begin{aligned}
2(3.4)^{2}-8(-0.8)^{2}&=18 \\
23.12-5.12&=18
\end{aligned}\]

\[2x^{2}-8y^{2}=18\\
x=5, \quad y=-2\]

\[\begin{aligned}
2(5)^{2}-8(-2)^{2}&=18 \\
50-32&=18
\end{aligned}\]

Both are valid so we can be confident our answer is correct.

Graphical representation

When graphed these two equations intersect at (3.4, − 0.8) and (5, − 2). So the solutions to the simultaneous equations are:

\[x= 3.4,y= -0.8\]

or

\[x=5,y=-2\]

**Negative numbers**

Making small mistakes when +, −, ✕, ÷ with negative numbers.

Remember when squaring a negative number you will get a positive.

**Missing solutions**

It is easy to forget that quadratic simultaneous equations can have two pairs of solutions. We need to use substitution to find all of the possible solutions.

**Not checking the answer using substitution**

Errors can quickly be spotted by substituting your solutions in the original first or second equations to check they work.

**Algebraic fractions**

When using algebraic fractions to remove the denominator make sure each term is carefully multiplied.

E.g.

\[2 x^{2}-\frac{49-42 x+9 x^{2}}{2}\\
4 x^{2}-(49-42 x+9 x^{2})\]

NOTE: multiply each term by

1. Solve the Simultaneous Equation:

\begin{aligned} &y=x+1 \\ &y=x^{2}+3 x-2 \end{aligned}

\begin{aligned}
&x=-1, \quad y=-2 \\
&x=-3, \quad y=-2
\end{aligned}

\begin{aligned}
&x=1, \quad y=2 \\
&x=3, \quad y=2
\end{aligned}

\begin{aligned}
&x=1, \quad y=2 \\
&x=-3, \quad y=-2
\end{aligned}

\begin{aligned}
&x=1, \quad y=-2 \\
&x=3, \quad y=-2
\end{aligned}

Because we know y=x+1 , we can substitute an expression for y into the second equation, so that x+1=x^{2}+3x-2 .

We then use our standard techniques to solve this quadratic equation. Substitute both answers for x into the first equation to find the necessary y values.

2. Solve the Simultaneous Equation:

\begin{aligned} x+y &=4 \\ y &=x^{2}+3 x-1 \end{aligned}

\begin{aligned}
&x=5, \quad y=9 \\
&x=1, \quad y=3
\end{aligned}

\begin{aligned}
&x=-5, \quad y=9 \\
&x=1, \quad y=3
\end{aligned}

\begin{aligned}
&x=-5, \quad y=9 \\
&x=-1, \quad y=-3
\end{aligned}

\begin{aligned}
&x=-5, \quad y=9 \\
&x=1, \quad y=-3
\end{aligned}

Rearranging the first equation gives y=4-x

We can substitute this into the second equation, giving 4-x=x^{2}+3 x-1

We then use our standard techniques for solving quadratic equations. Substitute both answers for x into the first equation to work out the necessary y values.

3. Solve the Simultaneous Equation:

\begin{aligned} y &=9 x^{2}+11 x+3 \\ 5 x-y &=-2 \end{aligned}

x=-\frac{1}{3},\quad y=\frac{1}{3}

x=-\frac{1}{3},\quad y=-\frac{1}{3}

x=\frac{1}{3},\quad y=\frac{1}{3}

x=\frac{1}{3},\quad y=-\frac{1}{3}

Rearranging the first equation gives y=5x+2

We can substitute this into the second equation, giving 5x+2=9 x^{2}+11 x+3

We then use our standard techniques for solving quadratic equations. This equation has a repeated root, so there is only one pair of solutions.

There is only one pair of solutions so the graphs only intersects at one point.

4. Solve the Simultaneous Equation:

\begin{aligned} y &=x-2 \\ 2 x^{2}-x y &=11 \end{aligned}

\begin{aligned}
&x=4.5, \quad y=6.5 \\
&x=2.5, \quad y=0.5
\end{aligned}

\begin{aligned}
&x=-4.5, \quad y=-6.5 \\
&x=-2.5, \quad y=-0.5
\end{aligned}

\begin{aligned}
&x=4.5, \quad y=-6.5 \\
&x=2.5, \quad y=-0.5
\end{aligned}

\begin{aligned}
&x=-4.5, \quad y=-6.5 \\
&x=2.5, \quad y=0.5
\end{aligned}

Substituting the first equation into the second gives 2 x^{2}-x (x-2) =11 or x^{2}+2x-11=0 .

We then use our standard techniques for solving quadratic equations. This can be solved by completing the square, but it is probably easier to use the quadratic formula in this case.

Substitute both answers for x into the first equation to work out the necessary y values.

1. Solve the simultaneous equations:

\begin{aligned} x y &=12 \\ y-3 x+9 &=0 \end{aligned}

**(7 marks)**

Show answer

Rearranging second equation to y = 3x − 9

**oe (1)**

Substitution of (3x − 9) into equation one

**(1)**

Correct expansion of bracket, e.g.

3 x^{2}-9 x=12**(1)**

Equation = 0

**(1)**

Solving for x correctly ( 4 and 1 )

Correct substitution of x back into either equation

**ft (1)**

Correct final answered clearly displayed

\begin{aligned} &x=4, \quad y=3 \\ &x=-1, \quad y=-12 \end{aligned}**(2)**

2. Solve the simultaneous equations:

\begin{aligned} a^{2}+b^{2}&=20 \\ b+10&=2 a \end{aligned}

**(5 marks)**

Show answer

Clear attempt for substitution of (10 − 2a) into first equations

**(1)**

Correct expansion of at least 3 terms of (10 − 2a)^{2} seen

100-20 a-20 a+4 a^{2}**(1)**

Simplifying to:

5 a^{2}-40 a+80 \text { or } a^{2}-8 a+16**(1)**

Correct substitution of a back into either equation for b

**ft (1)**

Correct final answered clearly displayed

a= 4 , b=-2**(1)**

3. Solve algebraically the simultaneous equations. You must show your working out at each stage:

\begin{aligned} x^{2}-4 y^{2}&=9 \\ 3 x+4 y&=7 \end{aligned}

**(6 marks)**

Show answer

A method to find an expression for y to substitute into first equations

E.g.

y=\frac{7-3 x}{4}**(1)**

Correct substitution and expansion

E.g.

x^{2}-4\left(\frac{49-42 x+9 x^{2}}{16}\right)=9or

4 x^{2}-49+42 x-9 x^{2}=36**(1)**

Correct attempt to form a quadratic equation

E.g.

5 x^{2}-42 x+85=0**(1)**

Correct method for solving quadratic equations

**(1)**

Correct final answered clearly displayed

\begin{aligned} &x=\frac{17}{5}, y=-\frac{4}{5} \\ &x=5, y=-2 \end{aligned}**(2)**

- Solve two simultaneous equations with two variables (where one equation is linear and the other is quadratic) algebraically

- Quadratic graphs
- Completing the square

Prepare your KS4 students for maths GCSEs success with Third Space Learning. Weekly online one to one GCSE maths revision lessons delivered by expert maths tutors.

Find out more about our GCSE maths revision programme.